(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
Most conversations about open recognition focus on education, employability, and institutional frameworks. While important, this framing overlooks the immediate economic realities faced by Africa’s millions of informal micro-entrepreneurs, for whom recognition has tangible value only when it unlocks finance, procurement opportunities, and market access. In South Africa, township businesses frequently encounter high loan rejection rates not because of lack of capability, but because entrepreneurial learning and operational competencies remain invisible to formal systems of trust. This presentation introduced the South Africa Digital Credentials for Finance model, a multi-stakeholder pilot designed to translate real-world entrepreneurial competencies into verifiable credentials that financial institutions and corporate buyers can recognize and trust. The model combines GrowthWheel’s internationally recognized 360° business assessment framework with digital credentialing infrastructure delivered through Open CPD [Continuing Professional Development]. Together, these systems create a pathway in which learning demonstrated through business practice is documented, validated, and issued as tamper-proof certificates, and badges that are portable, accessible, and auditable. Enterprise Support Organizations in South Africa use GrowthWheel to structure advisory engagements across key business domains, including operations, organization, client relations, and strategy. Advisors map entrepreneurial progress against these frameworks and issue credentials through Open CPD that are delivered via mobile-first channels such as email and messaging platforms. This ensures accessibility while enabling lenders, corporates, and ecosystem partners to observe verified engagement and competency development. The pilot is deliberately ecosystem-driven. Corporate supply chain actors validate credentials in procurement contexts, banking partners connect recognition to financial inclusion initiatives, universities provide independent evaluation, and professional organizations support standards alignment. Early case studies demonstrate that entrepreneurs holding GrowthWheel-verified credentials are beginning to leverage them to improve access to corporate opportunities and strengthen financing applications. Beyond finance, recognized competencies contribute to employability and resilience, addressing systemic drivers of small business failure. The model aligns with broader global priorities around digital public infrastructure, financial inclusion, and alternative data in small enterprise financing. It reflects policy directions emphasizing support for underserved entrepreneurs, women, and youth, while demonstrating how open recognition can function as infrastructure bridging informal and formal economies. The central proposition is simple: recognition must move beyond educational signaling to become economically actionable. When credentials are trusted by lenders and buyers, entrepreneurial capability becomes visible capital. Recognition that entrepreneurs can "bank on" transforms learning into opportunity, positioning open recognition as a practical engine for inclusive economic participation. Keywords: digital public infrastructure, invisible skills, entrepreneurial learning, continuing professional development, financial competencies